Studi Etnomatematika pada Tebar Padi di Pawinian dalam Pertanian Masyarakat Kabupaten Bogor - apit supriatna (FKIP Universitas Muhammadiyah Sukabumi, 2021)
The purpose of this research is to describe mathematical elemen in Bogor agricultural local wisdom, especially paddy seed spread on nursery as a step at paddy planting. This research use qualitative method with ethnographic study type which aim at getting become deep analitic and describe about ethnomathemathic in Bogor agricultural local wisdom. Collecting data is obtained from various sources are observation, interview, and literacy study technic, then reducting data, presentation, verification and drawing in a conclusion. The research partisipants were agricultural prominent figure who know and take care Bogor agricultural local wisdom. The result of this research show that there are mathematical elements in paddy seed spread on nursery activity such as ratio concept , mathematical terms, tessellation, geometry and congruent wide.